The Influence of Corporate Social Responsibility Disclosure, Dividend Policy, and Inflation on Stock Prices - Mustika, Sari; Alfiana, Yeni; Winarsih, Wiwin; Veronica, Aries; Dwiyanti; Allehandro, Reza (Universitas Indo Global Mandiri, 2025)
This study aims to determine the effect of CSR disclosure, dividend policy, and inflation on stock prices. The research design is causality research. The sample size was 40 companies in the food and beverage sector listed on the Indonesia Stock Exchange for the 2022-2024 period. The sampling technique used purposive sampling. The analysis technique used multiple linear regression. The analysis results found a CSR disclosure coefficient of 0.632, indicating no effect on stock prices. This indicates that the size of CSR does not directly impact stock prices. A company's CSR information is not a primary consideration for investors in making investment decisions. Furthermore, the analysis results show a Dividend Payout Ratio policy coefficient of 0.006, indicating an effect on stock prices. This indicates that the higher the dividends distributed to shareholders, the higher the company's stock price will be, as investors tend to value companies that provide stable and consistently increasing dividends. DPR is the percentage of a company's net profit paid to shareholders. This indicates a positive signal for the company's financial health. Furthermore, the inflation coefficient of 0.791 indicates that the inflation rate has no effect on stock prices. Continued inflation tends to cause stock prices to decline. This is caused by various factors, particularly a decline in public purchasing power. Simultaneously, all three independent variables influence stock prices. CSR disclosure, dividend policy, and inflation are economic factors that can influence stock prices. When these factors work together, their influence on stock prices can be more complex, but they can also create mutually supportive conditions for stock price increases. Keywords : Stock Price, CSR Disclosure, Dividend, Inflation